Mindfulness como técnica para mejorar la atención en procesos de aprendizaje en niños de primer grado de la Escuela “Sebastián de Benalcázar”, Bolívar, 2022-2023. - Andrade Medina, Sairy Dakilema (2023)
This research project aimed to investigate the effectiveness of mindfulness as a technique to improve attention in first-grade students at “Sebastián de Benalcázar” School in Bolivar during the 2022-2023 academic period. The study utilized a mixed approach that combined qualitative and quantitative elements. The primary objectives of the project were to determine the impact of attention on the learning process, provide theoretical justification for the use of mindfulness, and propose mindfulness activities to enhance attention during the learning process. The study recognized that a lack of attention and focus could significantly impede effective learning, and mindfulness is a powerful technique to improve students’ emotional health, focus, and retention of information. Mindfulness activities were implemented in the classroom during the research, and significant improvements in students’ attention and academic performance were observed. The study also found that the implementation of these activities could foster motivating experiences that enhance self-awareness, improve social skills, and promote teamwork. The implications of this study are significant, contributing to scientific knowledge on the use of mindfulness in the learning process, providing teachers with tools and strategies to improve student attention and learning, enhancing students’ emotional health, and strengthening their commitment to school activities to improve their academic performance and have a positive impact on their personal and professional lives